Improvement of Dental Composite Resin Using Supra -Nano Chicken thigh Bone Fibers - B. Lutfi, Rand; H. Jassim, Widad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Supra nanoparticles (submicron) of Chicken bones fibers were used (before and after treated with citric acid solution) as additives  to dental composite with the weight ratios (1%, 2% and 4%). The main mechanical tests represented by hardness, wear resistance and compression strength was carried out on the improvement dental composites.The addition of treated supra nanoparticles Chicken thigh bones with particles size (300 nm) by weight ratio (1%) to ordinary dental composite resin , significantly improves all of its mechanical properties, in addition to the increase the value of the its  glass transition temperature from  43oC  to 45.4 oC. The techniques X-ray diffraction (XRD), Energy Dispersive Spectroscopy (EDS) and Electron microscope images (SEM) were used to interpretation all the results that are improved mechanically and thermally.